(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2024)
This article analyzes the proposed amendments to art. 931 of the Civil Code within the context of legislative reform, focusing on the substitution of business owner liability for manufacturer liability and the introduction of the concept of "defect" as a requirement for strict liability, aligning the Civil Code regime with the Consumer Defense Code. Received in: July 2024 | Accepted in: October 2024